Criteria for clinical audit of women friendly care and providers' perception in Malawi - van den Broek Nynke; Kongnyuy Eugene J (BMC, 2008)
Abstract Background There are two dimensions of quality of maternity care, namely quality of health outcomes and quality as perceived by clients. The feasibility of using clinical audit to assess and improve the quality of maternity care as perceived by women was studied in Malawi. Objective We sought to (a) establish standards for women friendly care and (b) explore attitudinal barriers which could impede the proper implementation of clinical audit. Methods We used evidence from Malawi national guidelines and World Health Organisation manuals to establish local standards for women friendly care in three districts. We equally conducted a survey of health care providers to explore their attitudes towards criterion based audit. Results The standards addressed different aspects of care given to women in maternity units, namely (i) reception, (ii) attitudes towards women, (iii) respect for culture, (iv) respect for women, (v) waiting time, (vi) enabling environment, (vii) provision of information, (viii) individualised care, (ix) provision of skilled attendance at birth and emergency obstetric care, (x) confidentiality, and (xi) proper management of patient information. The health providers in Malawi generally held a favourable attitude towards clinical audit: 100.0% (54/54) agreed that criterion based audit will improve the quality of care and 92.6% believed that clinical audit is a good educational tool. However, there are concerns that criterion based audit would create a feeling of blame among providers (35.2%), and that manager would use clinical audit to identify and punish providers who fail to meet standards (27.8%). Conclusion Developing standards of maternity care that are acceptable to, and valued by, women requires consideration of both the research evidence and cultural values. Clinical audit is acceptable to health professionals in Malawi although there are concerns about its negative implications to the providers.